Supplementary material 1 from: Saarela JM, Sokoloff PC, Gillespie LJ, Bull RD (2023) Vascular plant biodiversity of Katannilik Territorial Park, Kimmirut and vicinity on Baffin Island, Nunavut, Canada: an annotated checklist of an Arctic flora. PhytoKeys 217: 1-135. https://doi.org/10.3897/phytokeys.217.90573 - Saarela, Jeffery M.; Sokoloff, Paul C.; Gillespie, Lynn J.; Bull, Roger D. (Zenodo, 2023)
Dataset of herbarium specimens documenting the vascular plant flora of Kattanilik Territorial Park and Kimmirut and vicinity, Baffin Island, Nunavut, Canada